FORMULASI DAN EVALUASI SEDIAAN KRIM PELEMBAB DARI SARI BIJIMARKISA UNGU (Passiflora edulis Sims.) DENGAN METODE INFUNDASI - Lisa Angrayani; Samran, Sofia Rahmi (Jurnal Kesehatan, 2023)
Purple passionfruit (Passiflora edulis Sims.) seeds have the potential to produce fatty oil that can be used as a carrier for cream preparations and can moisturize the skin. The cream preparation used in this study was a moisturizing cream. The purpose of this study was to determine whether the purple passion fruit seed extract can be used as a carrier and moisturizing agent in the preparation of moisturizing cream. This research method is experimental, starting with simplicia characterization, extracting purple passionfruit seeds with the infundation method, phytochemical screening, and formulating purple passion fruit seed extract with a concentration of 0; 10; 20; and 30% in moisturizing cream preparations. Evaluation of moisturizing cream preparations carried out included organoleptic examination of preparations and hedonic tests, determination of pH of preparations, stability tests of preparations, emulsion type tests of preparations, and irritation tests. The results of simplicia characterization showed that purple passionfruit seeds contained 3.73% water content; water-soluble extract content of 17.48%; the content of soluble extract in ethanol 16.65%; total ash content of 9.97%; and 0.98% acid insoluble ash content. The results of phytochemical screening showed that purple passion fruit seeds contained alkaloid compounds; flavonoids; saponins; and steroids/triterpenoids. The results of the evaluation of the moisturizing cream preparations showed that the cream was stable, both in terms of color, aroma, shape, and homogeneity in 12 weeks of storage at room temperature; the hedonic test showed that FIII was the preferred formula by the panelists; pH is still in the range of 4.5-6.5; emulsion type w/o; irritation test which showed negative values in volunteers. Based on the evaluation results of moisturizing preparations, purple passion fruit seed extract can be used as a carrier for cream preparations.